Effects of 4-week impairment-based rehabilitation on jump-landing biomechanics in chronic ankle instability patients. (March 2021) - Feger, Mark A.; Donovan, Luke; Herb, C. Collin; Hart, Joseph M.; Saliba, Susan A.; Abel, Mark F.; Hertel, Jay
Abstract: Objective: To determine effects of 4-weeks of impairment-based rehabilitation on lower extremity neuromechanics during jump-landing. Design: Descriptive laboratory study. Participants: Twenty-six CAI subjects (age = 21.4 ± 3.1 sex=(M = 7, F = 19), height = 169.0 ± 8.8 cm, weight = 71.0 ± 13.8 kg) completed 15 jump-landing trials prior to and following 12 supervised rehabilitation sessions. Main outcome measures: Frontal and sagittal lower extremity kinematics and kinetics and sEMG amplitudes (anterior tibialis, peroneus brevis, peroneus longus, and medial gastrocnemius). Means and 90% confidence intervals (CIs) were calculated for 100 ms prior to and 200 ms following ground contact. Areas where pre- and post-rehabilitation CIs did not overlap were considered significantly different. Kinematic and kinetic peaks and kinematic excursion were compared with paired t -test (P ≤ 0.05). Results: Following rehabilitation, CAI subjects exhibited less ankle (2.1° (0.8, 3.4), P < 0.01) and hip (2.0° (0.5, 3.7), P = 0.01) frontal plane excursion and lower peak hip abduction (2.5° (0.0, 5.0), P = 0.05). There was less ankle (5.0° (1.7, 8.3), P < 0.01) and knee (3.4° (0.8, 6.0), P = 0.01) sagittal plane excursion following rehabilitation. There was decreased peroneus longus activity from 9 ms to 135 ms post ground contact and decreased peak plantar flexion moment (0.08 N∗m/kg (0.01, 0.13), P = 0.02) following rehabilitation. Conclusion: Progressive impairment-based rehabilitation resulted in reductions in kinematic excursion and peroneus longus muscle activity, suggesting a more efficient landing strategy. Highlights: CAI patients exhibit less frontal plane ankle excursion following rehabilitation. Rehabilitation for CAI does not improve joint position prior to landing. CAI patients exhibit persistent alterations in landing neuromechanics after rehab.